2006
DOI: 10.1016/j.neuron.2006.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Rewarding and Aversive Outcomes on Activity in Macaque Lateral Prefrontal Cortex

Abstract: Both appetitive and aversive outcomes can reinforce animal behavior. It is not clear, however, whether the opposing kinds of reinforcers are processed by specific or common neural mechanisms. To investigate this issue, we studied macaque monkeys that performed a memory-guided saccade task for three different outcomes, namely delivery of liquid reward, avoidance of air puff, and feedback sound only. Animals performed the task best in rewarded trials, intermediately in aversive trials, and worst in sound-only tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 39 publications
6
78
0
1
Order By: Relevance
“…This type of neuron may be more concerned with differentiating competitive from noncompetitive situations than with differentiating between positive and negative outcomes. Similar valenceindependent, outcome-related neuronal activities were reported previously in LPFC (Kobayashi et al, 2006). Also, previous studies reported that LPFC neurons show contextdependent activities (White and Wise, 1999;Wallis et al, 2001;Watanabe et al, 2002;Amemori and Sawaguchi, 2006a,b;IchiharaTakeda and Funahashi, 2008;Kennerley and Wallis, 2009), which are related to coding cognitive and/or motivational context information.…”
Section: Discussionsupporting
confidence: 83%
“…This type of neuron may be more concerned with differentiating competitive from noncompetitive situations than with differentiating between positive and negative outcomes. Similar valenceindependent, outcome-related neuronal activities were reported previously in LPFC (Kobayashi et al, 2006). Also, previous studies reported that LPFC neurons show contextdependent activities (White and Wise, 1999;Wallis et al, 2001;Watanabe et al, 2002;Amemori and Sawaguchi, 2006a,b;IchiharaTakeda and Funahashi, 2008;Kennerley and Wallis, 2009), which are related to coding cognitive and/or motivational context information.…”
Section: Discussionsupporting
confidence: 83%
“…In sum, the expected value of engaging different neuronal populations, dedicated to specific tasks, might be topographically represented in frontostriatal circuits. In primate prefrontal cortex or striatum, certain neuronal activities have been reported to express both expected reward and various task dimensions, such as target location (Watanabe, 1996;Leon and Shadlen, 1999;Kobayashi et al, 2006) or movement direction (Lauwereyns et al, 2002;Matsumoto et al, 2003;Samejima et al, 2005;Pasquereau et al, 2007). However, the topographical organization of neuronal populations encoding expected values, and their connection with the corresponding effectors, remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fMRI meta-analyses suggest that brain areas that code for both rewards and punishments are the exception rather than the norm (Bartra, McGuire, & Kable, 2013;Garrison, Erdeniz, & Done, 2013). Similarly, single cell studies show that neurons that fire in response to reward or punishment only are markedly more common than those that raise their firing in response to rewards and reduce it in response to punishments (Kobayashi et al, 2006). Furthermore, it has been argued that the dissociation of reward and punishment is neurochemically instantiated, with dopamine coding reward and serotonin coding punishment (Daw, Kakade, & Dayan, 2002).…”
Section: Introductionmentioning
confidence: 99%